The impact of interest rates on household debt accumulation in Malaysia: a structural break analysis. (24th January 2020) - Khan, Hafizah Hammad Ahmad; Abdullah, Hussin; Samsudin, Shamzaeffa
This study aims to investigate the long run impact of the cost of borrowing on the household debt in Malaysia in order to determine whether the interest rate targeting method could provide solutions to control high debt accumulation. By using the autoregressive distributed lag (ARDL) model with structural break, findings of this study suggest that, although the cost of borrowing has a negative impact on household debt, the effect is relatively low compared to the income level, housing markets and demographic effects on the debt accumulation. As a result, the low interest rate policy adopted by the country since the Asian Financial Crisis is not the basis that brings towards the bulk of household debt in the country and thereby the interest rate targeting method is not the effective mechanism to control the high debt level.